2016
DOI: 10.1177/0148607116657648
|View full text |Cite
|
Sign up to set email alerts
|

Can We Rely on Predicted Basal Metabolic Rate in Patients With Intestinal Failure on Home Parenteral Nutrition?

Abstract: The Harris-Benedict and Johnstone equations reliably predict BMR in two-thirds of clinically stable patients with IF on HPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…– Three studies ( n = 192), mean results comparable, reported as total daily amounts (1131–1311 kcal/day) 43–45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…– Three studies ( n = 192), mean results comparable, reported as total daily amounts (1131–1311 kcal/day) 43–45 …”
Section: Resultsmentioning
confidence: 99%
“…Three studies measured resting energy expenditure using indirect calorimetry 43–45 . Measurement conditions were inconsistent and, although variation between measured and predicted energy expenditure was shown, different prediction equations and limits of agreement were used.…”
Section: Resultsmentioning
confidence: 99%
“…According to surveys and guidelines, HPN patients in general are to be surrounded by well-trained health care providers and to visit the hospital on a regular basis for the evaluation of nutritional status and possible interventions to enhance patients’ outcomes [ 8 , 18 , 48 ]. Since IF patients’ metabolisms change over time and vary in between patients [ 1 ], it is important to define REE at start-up and redefine during follow-up, particularly in long-term (>6 months) HPN patients. This allows for an individualized energy dosing plan.…”
Section: Ic From Bench To Bedsidementioning
confidence: 99%
“…Patients with a dysfunctional gastrointestinal system, for example, intestinal failure (IF), can be malnourished when the physiological demand of nutrients is higher than the nutritional intake [ 1 ]. IF is characterized by malabsorption leading to diarrhea and dehydration, making IF one of the indications for treatment with parenteral nutrition (PN) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation